2020
DOI: 10.1186/s12916-020-01797-2
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk factors and their effects on survival: a Mendelian randomisation study

Abstract: Background Observational studies have investigated the association of risk factors with breast cancer prognosis. However, the results have been conflicting and it has been challenging to establish causality due to potential residual confounding. Using a Mendelian randomisation (MR) approach, we aimed to examine the potential causal association between breast cancer-specific survival and nine established risk factors for breast cancer: alcohol consumption, body mass index, height, physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 67 publications
1
34
0
Order By: Relevance
“…While little is known about this proline form, studies for the close family member PYCR1 have found that higher levels of mRNA were associated with reduced survival from breast cancer patients 26 . To support further our hypothesis that the two genome-wide significant SNPs (rs138569520 and rs146023652) were specific for survival in patients with metastatic disease, we confirmed that there were no associations (HR = 1.04, P = 0.58, MAF = 0.02 and HR = 1.03, P = 0.60, MAF = 0.02 respectively) with breast cancer-specific survival in the most recent BCAC dataset for all invasive early (stages I–III) breast cancers (OncoArray and iCOGS, n = 86,627) 27 .…”
Section: Discussionsupporting
confidence: 68%
“…While little is known about this proline form, studies for the close family member PYCR1 have found that higher levels of mRNA were associated with reduced survival from breast cancer patients 26 . To support further our hypothesis that the two genome-wide significant SNPs (rs138569520 and rs146023652) were specific for survival in patients with metastatic disease, we confirmed that there were no associations (HR = 1.04, P = 0.58, MAF = 0.02 and HR = 1.03, P = 0.60, MAF = 0.02 respectively) with breast cancer-specific survival in the most recent BCAC dataset for all invasive early (stages I–III) breast cancers (OncoArray and iCOGS, n = 86,627) 27 .…”
Section: Discussionsupporting
confidence: 68%
“…The rapid increase in the number of features from different data sources and the use of heterogeneous features have led to great challenges in survival prediction. With the deepening of research on breast cancer, many new variables that are significantly related to breast cancer prognosis have been gradually discovered [14,76,77], such as the level of anxiety and depression. Thus, the above factors should be taken into account in the prediction.…”
Section: Plos Onementioning
confidence: 99%
“…An increase in the number of reported cases and deaths has inspired numerous studies to understand the disease characteristics, causal associations and suitable solutions to mitigate this public health problem. In addition to established risks e.g., higher chronological age [ 5 ], genetic influence [ 6 ], and being non-Hispanic white [ 5 ], several environmental factors [ 7 ] play a crucial role beneath in the underlying mechanism. Weight and diet are important environmental factors that influence plasma lipids and lipoproteins, and their role in breast cancer incidence has been a relatively new concept in recent years [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%